The Impact of Adoption of Islamic Instruments (Ughods) on Profitability: the Case of Islamic Banks in Malaysia - Zaini, Syeliya Md; Zandi, GholamReza; Ruhoma, Alseddig; Amin, Mohammad (International Journal of Engineering and Technology, 2018)
Currently many Islamic Banks started on the development of new products the Islamic Instrument (Ughod) such as of Ijarah, Mudharabah, Murabahah and Musharakah. The main aim of this paper is to know the effect of the application of Islamic Instruments (Ughod) and their diversity in improving the profitability rates of Malaysian Islamic banks. This study was confined to two banks of Hong Leong Islamic and HSBC Amanah Islamic Bank, during the period 2009-2013. The sample-included data collected from the actual financial reports and the financial statements issued by chosen the Banks. The study was adopted in order to achieve the objectives and reach the results on the descriptive and analytical method, where used the simple linear regression and multiple to test the hypothesis of the study and answer the questions of the study. The results of the analysis of both banks showed that adoption Islamic instruments (Ughods) in banking transactions. Our results also showed the existence of a statistical impact of the application of Islamic Instruments (Ughod) on the profitability rates of Islamic Banks, despite the Global Financial Crisis that stroked many conventional banks. This emphasized on the efficiency of the Islamic banking system for Risk Management during the financial crises. The adoption of the application of Islamic instruments in banking transactions which provided by the Islamic banking system would enhance the profitability of banks and making the banks in a safe status during financial fluctuations.